Wykluczenie bonum sacramenti w wyroku Roty Rzymskiej c. Erlebach z dnia 3 lutego 2011 roku - Góralski, Wojciech (Ius Matrimoniale, 2019)
The author presents provides a commentary on the judgment (a negative) nullitatis matrimonii oft the Roman Rota c. Erlebach, passed 3.02.2011 (in the third instance) by a turnus of auditors coram Erlebach on the grounds of exclusion of the indissolubility of marriage (from the archidiocese of Montevideo). The court of first instance passed a positive judgment and the second instance court issued a negative judgment. The case concerns a marriage concluded in 1973 by a man who was permeated by Marxist philosophy, rejected God and religion, and even marriage. The man married under the pressure of the fiancé’s family as well as for obtaining material benefits. Both the court testimonies of the man and the witnesses (the woman defendant refused to testify) they did not let you know the plaintiff’s will. It was also missing causa proxima exclusion of bonum sacramnti, as well as circumstances pro simulatione; moreover, many circumstances deny the simulation. The verdict c. Erlebach is an example of an in-depth assessment of the evidence, which showed the views and beliefs of the man, but did not show a positive act of will.